A Hybrid Approach Combining Dual-Energy and Inpainting Methods for Metal Artifact Reduction in Dentomaxillofacial CBCT: A Proof-of-Concept Phantom Study - Jayakody, Dinidu; Agrawal, Harshit; Räinä, Ella; Sipola, Annina; Näpänkangas, Ritva; Ylisiurua, Sampo; Nieminen, Miika T.; Brix, Mikael (Annals of biomedical engineering, 2025)
Image inaccuracies and distortions are amplified in cone-beam computed tomography (CBCT), with beam hardening and metal artifacts being particularly pronounced, thereby complicating diagnostic interpretation. An approach, combining dual-energy CBCT based projection-domain material decomposition with virtual monochromatic imaging (VMI) technique, was leveraged to mitigate beam hardening artifacts originating from dental restorative and prosthetic materials on a diagnostic CBCT scanner in a phantom setting. Severe artifact-causing dental restorative and prosthetic materials were identified from the literature and six of them were selected for the study. Six different phantoms were developed using selected materials, and 3D-printed cylindrical molds filled with gelatine. Three different tube voltages, such as 80 kilovoltage (kV), 100 kV, 120 kV were selected for scanning and the phantoms were scanned using a commercial CBCT scanner (Viso G7, Planmeca Oy., Helsinki, Finland). A custom-developed material decomposition algorithm, based on polychromatic projection domain modeling, was employed to separate the dual-energy data into water and iron basis materials. VMIs were then synthesized at 200 keV using the decomposed data. For comparison, the 100 kV acquisition (routine protocol) with and without the vendor's inpainting-based MAR algorithm was used to assess VMI techniques' performance for artifact reduction. Both subjectively and quantitatively, the VMI technique offered better image quality than the routine 100 kV protocol. Further, combining the VMI technique with an inpainting-based MAR algorithm offered superior artifact reduction (p < 0.01) for all tested materials compared to using the routine protocol and the MAR algorithm. The proposed VMI + MAR technique offered superior artifact reduction compared to a commercial MAR algorithm.